The Impact Of Chronic Diseases On The Quality Of Life Among The Elderly People In The East Of Tehran - Davoud Shojaeizadeh; Sima Esmaeili Shahmirzadi; Kamal Azam; Leili Salehi; Azar Tol; Monavvar Moradian Sorkhkolaei (Tehran University of Medical Sciences, 2012)
Background and Aim: Increase in life expectancy is associated with non-communicable diseases. This study is aimed to survey the effect of chronic diseases on the quality of life among the elderly people in elderly care centers in the East of Tehran in 2011. Materials and Methods: This is an analytical study in which 424 people were randomly selected. They were members of elderly care centers and were 60 years of age or higher. The data collection instruments were a standard quality-of-life questionnaire(SF36) and a chronic diseases record checklist. The data were collected in an interview. For data analysis purposes, Independent T-Test, ANOVA, and Pearson correlation coefficient were used.Results: The mean age of participants was 67.34±7.16. Some 92.2% of patients were suffering from at least one chronic disease, and there was a significant statistical difference between the mean points of all aspects of quality of life of those suffering from chronic diseases and those without a history of chronic diseases(P<0.001). Moreover, there was a significant relationship between the quality of life on the one hand and gender, marital status, economic status, and education on the other(P<0.05). Conclusion: The findings show that an increase in the number of chronic diseases leads to a decrease in the quality of life, and that the application of appropriate educational and interventional approaches can help take effective steps to enhance the old people's health.